(untitled) (Practicum Psychologia, 2025)
This study investigated the moderating role of locus of control on the relationship between grit and test anxiety among undergraduates in public universities in Anambra State, Nigeria. Total of 381 undergraduates selected through simple random sampling and accidental sampling from Nnamdi Azikiwe University, Awka and Chukwuemeka Odumegwu Ojukwu university, igbariam served as participants. The sample comprised 134 males and 247 females, aged 18–37 years (M = 24.14, SD = 5.77). Standardized measures were utilized, including the Grit Scale (assessing perseverance and passion for long-term goals), the Test Anxiety Inventory (evaluating test anxiety levels), and Rotter’s Locus of Control Scale (determining internal versus external orientation). A correlational research design was employed, and Hierarchical linear regression analyses were conducted to test the study hypotheses. The findings revealed that grit negatively correlated with students’ test anxiety at (F2, 378), β= -.22, p<.01. Internal locus of control did not moderate the relationship between grit and test anxiety at (F6, 374), β= .02, p>.05. External locus of control moderated the relationship between grit and test anxiety at (F6, 374), β= .25, p<.01. These results highlighted the critical role of locus of control in shaping how grit influenced test anxiety. The study emphasized the need for interventions to develop grit while fostering locus of control to reduce test anxiety among students. Implications for educational practices, counselling strategies, and future research are discussed.